1994
DOI: 10.1037/0003-066x.49.12.1004
|View full text |Cite
|
Sign up to set email alerts
|

Psychoneuroimmunology: The interface between behavior, brain, and immunity.

Abstract: Psychoneuroimmunology is the study of interactions between behavior, the brain, and the immune system. This article is designed to provide an overview of this new field for the general psychologist. The existence of bidirectional communication pathways between the brain and the immune system and the implications of this network for behavior are emphasized. Implications are that behavioralpsychological processes ought to be capable of altering immune function and that events that occur as part of immune respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
175
0
9

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 326 publications
(186 citation statements)
references
References 83 publications
(100 reference statements)
2
175
0
9
Order By: Relevance
“…The reference lists of 11 review articles on stress and the immune system (Benschop, Geenen, et al, 1998;Biondi, 2001;Cacioppo, 1994;S. Cohen & Herbert, 1996;Herbert & Cohen, 1993;Kiecolt-Glaser, Cacioppo, Malarkey, & Glaser, 1992;Kiecolt-Glaser, McGuire, Robles, & Glaser, 2002;Maier, Watkins, & Fleshner, 1994;O'Leary, 1990;Zorrilla et al, 2001) were then searched to identify additional articles.We selected only articles that met a number of inclusion criteria. The first criterion was that the work had to include a measure of stress.…”
mentioning
confidence: 99%
“…The reference lists of 11 review articles on stress and the immune system (Benschop, Geenen, et al, 1998;Biondi, 2001;Cacioppo, 1994;S. Cohen & Herbert, 1996;Herbert & Cohen, 1993;Kiecolt-Glaser, Cacioppo, Malarkey, & Glaser, 1992;Kiecolt-Glaser, McGuire, Robles, & Glaser, 2002;Maier, Watkins, & Fleshner, 1994;O'Leary, 1990;Zorrilla et al, 2001) were then searched to identify additional articles.We selected only articles that met a number of inclusion criteria. The first criterion was that the work had to include a measure of stress.…”
mentioning
confidence: 99%
“…A lthough it has long been apparent that the immune system and the brain are closely connected, and rapid progress in our understanding of the molecules involved in regulating both immune and neural functions has been made, the extent and the exact mechanisms of this connection are still matters of considerable debate (1). One of the most likely mediators for communication between these two systems is the cytokine network because both neural and immune cells express cytokine receptors that regulate numerous aspects of cell function such as survival, differentiation, and motility.…”
mentioning
confidence: 99%
“…Stress is suspected to play a role in the etiology of many diseases, and numerous elegant studies have shown that stress can be immunosuppressive and, hence, may be detrimental to health (5)(6)(7)(8)(9)(10)(11)(12). However, we have suggested that, under certain conditions, a stress response may enhance immune function and prepare the immune system for challenges (e.g., wounding or infection) that may be imposed by a stressor, just as a stress response prepares the nervous, cardiovascular, musculoskeletal, and neuroendocrine systems for fight or flight (1,3,(13)(14)(15).…”
mentioning
confidence: 99%